Frontline Science: Targeted expression of a dominant-negative high mobility group A1 transgene improves outcome in sepsis (2018)
High mobility group (HMG) proteins are a family of architectural transcription factors, with HMGA1 playing a role in the regulation of genes involved in promoting systemic inflammatory responses. We speculated that blocking HMGA1?mediated pathways might improve outcomes from sepsis. To investigate HMGA1 further, we developed genetically modified mice expressing a dominant negative (dn) form of HMGA1 targeted to the vasculature. In dnHMGA1 transgenic (Tg) mice, endogenous HMGA1 is present, but its function is decreased due to the mutant transgene. These mice allowed us to specifically study the importance of HMGA1 not only during a purely pro?inflammatory insult of endotoxemia, but also during microbial sepsis induced by implantation of a bacterial?laden fibrin clot into the peritoneum. We found that the dnHMGA1 transgene was only present in Tg and not wild?type (WT) littermate mice, and the mutant transgene was able to interact with transcription factors (such as NF??B), but was not able to bind DNA. Tg mice exhibited a blunted hypotensive response to endotoxemia, and less mortality in microbial sepsis. Moreover, Tg mice had a reduced inflammatory response during sepsis, with decreased macrophage and neutrophil infiltration into tissues, which was associated with reduced expression of monocyte chemotactic protein?1 and macrophage inflammatory protein?2. Collectively, these data suggest that targeted expression of a dnHMGA1 transgene is able to improve outcomes in models of endotoxin exposure and microbial sepsis, in part by modulating the immune response and suggest a novel modifiable pathway to target therapeutics in sepsis.